Gallium Nitride Materials and Devices XIV 2019
DOI: 10.1117/12.2506210
|View full text |Cite
|
Sign up to set email alerts
|

Functional integrity and stable high-temperature operation of planarized ultraviolet-A AlxGa1−xN/AlyGa1−yN multiple-quantum-disk nanowire LEDs with charge-conduction promoting interlayer

Abstract: CitationAlfaraj N, Alhamoud AA, Priante D, Janjua B, Alatawi AA, et al.Functional integrity and stable high-temperature operation of planarized ultraviolet-A AlxGa1−xN/AlyGa1−yN multiplequantum-disk nanowire LEDs with charge-conduction promoting interlayer. Gallium Nitride Materials and Devices XIV. Available: http://dx.ABSTRACT Unprecedented high-temperature operational stability of interfacial silicide-free ultraviolet-A multiple-quantumdisk AlGaN nanowire-based light-emitting diodes on metal is achieved and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Deep-ultraviolet photodetectors (PDs) incorporating beta-polymorph gallium oxide (β-Ga 2 O 3 ) thin films have been the subject of extensive studies since the introduction of epitaxial deposition techniques for group III–oxide materials because of the enhancements in photosensitivity and solar-blind photodetection characteristics. Although β-Ga 2 O 3 /NiO heterostructures have been investigated by various research groups, none of these studies provided details about the epitaxial growth process supported by electron microscopy imaging or applied and comprehensive optoelectrical device fabrication and characterization. With regards to optoelectronic applications, the majority of research groups have so far focused on the relatively narrow-band gap gallium/aluminum nitride (Ga­(Al)­N)-based devices that exhibit varying degrees of operational stability and ultrawide-band gap group III–oxides-based devices grown and fabricated directly on bulk α-Al 2 O 3 (sapphire) . Han et al have demonstrated solar-blind deep-ultraviolet Mg 0.58 Zn 0.42 O Schottky-type metal–semiconductor–metal (MSM) PDs grown on (100) magnesium oxide (MgO) substrates with an MgO buffer layer .…”
Section: Introductionmentioning
confidence: 99%
“…Deep-ultraviolet photodetectors (PDs) incorporating beta-polymorph gallium oxide (β-Ga 2 O 3 ) thin films have been the subject of extensive studies since the introduction of epitaxial deposition techniques for group III–oxide materials because of the enhancements in photosensitivity and solar-blind photodetection characteristics. Although β-Ga 2 O 3 /NiO heterostructures have been investigated by various research groups, none of these studies provided details about the epitaxial growth process supported by electron microscopy imaging or applied and comprehensive optoelectrical device fabrication and characterization. With regards to optoelectronic applications, the majority of research groups have so far focused on the relatively narrow-band gap gallium/aluminum nitride (Ga­(Al)­N)-based devices that exhibit varying degrees of operational stability and ultrawide-band gap group III–oxides-based devices grown and fabricated directly on bulk α-Al 2 O 3 (sapphire) . Han et al have demonstrated solar-blind deep-ultraviolet Mg 0.58 Zn 0.42 O Schottky-type metal–semiconductor–metal (MSM) PDs grown on (100) magnesium oxide (MgO) substrates with an MgO buffer layer .…”
Section: Introductionmentioning
confidence: 99%
“…These properties motivated the intense research of NW flexible LEDs [4,[8][9][10][11][12][13]16]. In most realizations, NWs are embedded in a transparent polymer (e.g., polydimethylsiloxane (PDMS), polyimide, SU-8, or parylene [12,[17][18][19][20][21]), which acts as a supporting material to form the active membrane. While III-V material composing NWs has a long lifetime and can withstand high temperatures, the embedding polymer is prone to degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet (UV)-emitting group III-nitride materials hold a promising potential for a variety of multifunctional applications, including solid-state lighting technology [1][2][3][4] and water purification and disinfection [5,6] . With the wide range of wavelength tunability available to UV-emitting group III-nitride materials, the most promising germicidal ultraviolet devices are found in aluminum gallium nitride and its alloys (Al x Ga 1−x N, where 0 < x < 1), and one of the most crucial applications of Al x Ga 1−x N-based devices is water sterilization [7][8][9][10] , particularly for highly water-stressed countries. Group III-nitride materials are chemically and thermally robust [11][12][13] , exhibit long carrier lifetimes [14] , are operationally stable [15] , and are the only known materials that have wide and direct bandgaps and are wavelength-tunable within the UV regime of operation (from around 200 to 400 nm).…”
Section: Introductionmentioning
confidence: 99%